Management Development of Lecturers to Increase Research Quality at Stikom Uyelindo Kupang - Hasibun Asikin; Heni; Yakin A. Asikin (East Asian Journal of Multidisciplinary Research, 2022)
This research is motivated by the low quality and research culture of STIKOM Uyelindo Kupang lecturers. The purpose of this study is to determine the management of lecturer development by research institutions, to find out the goals and development programs, and to know the implementation and results of the coaching. The method used in this study is a qualitative descriptive method. The results of this research are: 1) private higher education and training institutions in East Nusa Tenggara have not maximally implemented lecturer development in an effort to improve research quality; 2) the implementation of the training has not been fully implemented by the research institute on the tertiary institution conducting research